2016
DOI: 10.1016/j.jaut.2016.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulators in SLE: Clinical evidence and immunologic actions

Abstract: Systemic lupus erythematosus (SLE) is a potentially fatal autoimmune disease. Current treatment strategies rely heavily on corticosteroids, which are in turn responsible for a significant burden of morbidity, and immunosuppressives which are limited by suboptimal efficacy, increased infections and malignancies. There are significant deficiencies in our immunosuppressive armamentarium, making immunomodulatory therapies crucial, offering the opportunity to prevent disease flare and the subsequent accrual of dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(42 citation statements)
references
References 141 publications
1
34
0
7
Order By: Relevance
“…The efficacy of HCQ may result from its ability to inhibit the activation of toll-like receptors (TLRs) and numerous cytokines [7], which are also crucial in the abnormal mucosa-kidney axis in IgAN [8]. Gao et al [9] found that HCQ reduced proteinuria to 65.9 ± 25.5% ( p = 0.002) of the baseline level (0.90 ± 0.45 g/day) in patients with IgAN; however, there was no statistically significant difference in proteinuria levels between the HCQ and losartan groups.…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of HCQ may result from its ability to inhibit the activation of toll-like receptors (TLRs) and numerous cytokines [7], which are also crucial in the abnormal mucosa-kidney axis in IgAN [8]. Gao et al [9] found that HCQ reduced proteinuria to 65.9 ± 25.5% ( p = 0.002) of the baseline level (0.90 ± 0.45 g/day) in patients with IgAN; however, there was no statistically significant difference in proteinuria levels between the HCQ and losartan groups.…”
Section: Introductionmentioning
confidence: 99%
“…23 Drugs decreasing virus shedding may therefore be inadequate at this stage; this is why many anti-inflammatory drugs are currently being tested, such as tocilizumab, corticosteroids, and others. Despite the immunomodulatory properties of HCQ, which include regulation of the production of pro-inflammatory cytokines such as IL-2, IL-1, IL-6 and TNFα, 24 and endosomal inhibition of toll-like receptors, which play a major role in innate immune response, 2 5…”
mentioning
confidence: 99%
“…Lupus nephritis started from the deposition of anti-dsDNA antibody immune complexes in the kidney parenchyma, which activated the complement system via classical pathway, induced the leucocytes infiltration to release inflammatory mediators (chemokines, proinflammatory cytokines, enzymes, and nitric oxide), and finally rendered the renal damage [2,3]. Although the initiating events are not completely understood, it is generally accepted that abnormally autoreactive T lymphocytes play an important role in disease pathogenesis and progress.…”
Section: Introductionmentioning
confidence: 99%